2005
DOI: 10.1590/s1679-62252005000300001
|View full text |Cite
|
Sign up to set email alerts
|

A new Synbranchus (Teleostei: Synbranchiformes: Synbranchidae) from ilha de Marajó, Pará, Brazil, with notes on its reproductive biology and larval development

Abstract: Synbranchus lampreia, new species, is described from rio Goiapi, Marajó Island, Pará, northern Brazil. It differs from the other two described species of the genus by its color pattern, which consists of large roundish black blotches scattered over a light brown or yellowish ground pigmentation and presence of inconspicuous brown small spots distributed among the large dark spots. The species is further distinguished from S. marmoratus by a higher number of vertebrae and from S. madeira by a shorter postanal l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 851 publications
(14 citation statements)
references
References 13 publications
0
13
0
1
Order By: Relevance
“…Eyes are protractile and visible from long distance in O. bengalense but in M. cuchia eye is small and visible only through a translucent layer of skin. Eyes are well developed, visible through a translucent layer of skin, and vertically aligned to posterior nostrils in Synbranchus lamperia (Favorito et al, 2005). The body length and weight are much greater in M. cuchia than in O. bengalense.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Eyes are protractile and visible from long distance in O. bengalense but in M. cuchia eye is small and visible only through a translucent layer of skin. Eyes are well developed, visible through a translucent layer of skin, and vertically aligned to posterior nostrils in Synbranchus lamperia (Favorito et al, 2005). The body length and weight are much greater in M. cuchia than in O. bengalense.…”
Section: Discussionmentioning
confidence: 97%
“…All over the body is triangular shape in M.cuchia and round in O.bengalense. Favorito et al (2005) reported that S. lampreia can be easily distinguished from S. marmoratus and S. madeirae by its color pattern which consists of conspicuous large black or dark brown, roundish blotches scattered along body, rare on head, and a relatively lighter ground coloration with small and inconspicuous light brown spots vs. more homogeneously distributed spots and marbled pattern in S. marmoratus and gray uniform coloration with lighter roundish spots in S. madeirae. The phenotypic plasticity of fish is very high.…”
Section: Discussionmentioning
confidence: 99%
“…Morphological differences between species in the Synbranchiformes order are commonly used in systematic and biogeographical studies (Rosen & Rumney, 1972;Rosen & Greenwood, 1976;Favorito et al, 2005). However, many morphological traits can be subtle or ambiguous, which often makes it difficult to recognize and describe new species.…”
Section: Discussionmentioning
confidence: 99%
“…Fishes belonging to the genus Synbranchus (Synbranchiformes, Synbranchidae) are currently divided into three recognized species: (1) S. madeirae Rosen & Rumney, 1972, which is restricted to the Madeira River basin; (2) S. lampreia Favorito, Zanata & Assumpção, 2005, which is restricted to Marajó Island; and (3) S. marmoratus Bloch, 1795, which is widely distributed throughout South and Central America (Rosen & Rumney, 1972). Although S. marmoratus specimens appear to belong to a single taxonomic group, some populations may display an extensive karyotype diversity, with diploid numbers ranging from 42 to 46 chromosomes; furthermore, variations in chromosome morphology as well as in the distribution of constitutive heterochromatin and rDNA genes have also been observed (Foresti et al, 1992;Melilo et al, 1996;Sanchez & Fenocchio, 1996;Torres et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Table 2 This species belongs to a species complex and is widely distributed in river drainages from Mexico to northern Argentina. It can be distinguished from its congeners by the color pattern which consists of more homogeneously distributed spots and marbled pattern along body, and by the number of vertebrae (116-150) (Favorito et al 2005).…”
Section: Family Rivulidaementioning
confidence: 99%